Yield Evaluation of Upland Rice Varieties (Oryza sativa L.) in Several Levels of Soil Water Content - Syarifa Mayly; Abdul Rauf; Chairani Hanum; Hamidah Hanum (Agro Bali : Agricultural Journal, 2023)
Production and productivity of upland rice is still very low due to limited water in the upland rice ecosystem. The objective of this study was to evaluate the yields of upland rice varieties at several levels of soil water content. The experiment was conducted at the Growth Centre LLDIKTI Wilayah I Medan from March to July 2013. This research used a factorial randomized block design with two factors and replicated three times. Five upland rice varieties as the first factor, namely Batutegi, Inpago 4, Limboto, Situbagendit, and Situpatenggang. Second factor was four levels of soil water content, namely: 80% of field capacity (FC), 60% of FC, 40% of FC, 20% of FC. The main effect of upland rice varieties and soil water content significantly affected (p<0.05) the productive tiller number, percentage of empty and filled grain, the panicle length, 1000 grain weight, and weight grain per clumps.   The interaction effect between upland rice varieties and soil water content showed significant interaction on the panicle length, 1000 grain weight, and weight grain per clumps. Situpatenggang variety showed the best yield characters like productive tiller number, percentage of empty and filled grain than the other four varieties. Combination treatment of Situpatenggang variety with 80% FC showed the highest panicle, 1000 grain weight, and weight grain per clumps. The smallest percentage decreased in grain yield per clumps due to decreased the level of soil water content was found in the Inpago 4 variety, so it can be recommended to plant Inpago 4 on soil which had low level of soil water content.